2022
DOI: 10.1039/d2bm00223j
|View full text |Cite
|
Sign up to set email alerts
|

A 3D printable perfused hydrogel vascular model to assay ultrasound-induced permeability

Abstract: The development of an in vitro model to study vascular permeability is vital for clinical applications such as the targeted delivery of therapeutics. This work demonstrates the use of a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…[ 77–79 ] The main reason pushing their exploitation is the preservation of a strong angiogenic activity, leading to their proliferation on lumen‐like structures, also in vitro. [ 80 ]…”
Section: Employed Technologies and Methods For The 3d‐bioprinting Of ...mentioning
confidence: 99%
See 1 more Smart Citation
“…[ 77–79 ] The main reason pushing their exploitation is the preservation of a strong angiogenic activity, leading to their proliferation on lumen‐like structures, also in vitro. [ 80 ]…”
Section: Employed Technologies and Methods For The 3d‐bioprinting Of ...mentioning
confidence: 99%
“…[77][78][79] The main reason pushing their exploitation is the preservation of a strong angiogenic activity, leading to their proliferation on lumen-like structures, also in vitro. [80] Liver sinusoids are also studded with Kupffer cells, which are hepatic macrophages. They regulate the immune response in the organ, and remove noxious compounds from the portal vein.…”
Section: Cells For Liver Bioinksmentioning
confidence: 99%
“…To overcome the above drawbacks, microfabricated chips were used to study the disruption of endothelial cell–cell contract ( Figure 9 , Figure 10 , Figure 11 and Figure 12 ) by ultrasound and microbubbles [ 21 , 37 , 101 , 125 , 126 ]. A typical setup for this type of experiment is illustrated in Figure 13 .…”
Section: Ultrasound-driven Microbubbles Reversibly Open Bbbmentioning
confidence: 99%
“…Royse et al [ 126 ] reported a perfusion-based 3D printable hydrogel vascular model to assess BBB permeability and its function. Ultrasound-driven microbubbles increased the permeability of the BBB, altered cell area, and disrupted cell–cell junctions.…”
Section: Ultrasound-driven Microbubbles Reversibly Open Bbbmentioning
confidence: 99%
See 1 more Smart Citation